Juvenile xanthogranuloma in an adult - Nayak Surajit; Acharjya Basanti; Devi Basanti; Patra Manoj (Wolters Kluwer Medknow Publications, 2009)
Juvenile xanthogranuloma (JXG), a rare benign histiocytic disorder, primarily seen in the first two decades of life as a solitary cutaneous lesion. Though in majority of cases lesions are confined to the skin, systemic forms can occur in rare instances. We present here a 21-year-old male patient presenting with multiple brown-to-yellowish papules and nodules over the head, neck and trunk evolving since last 2 years. A clinico/histopathologic study was done to confirm the diagnosis of JXG. We present this case, because of the unusual presentation and morphology in regards to the age and to highlight the fact that, juvenile xanthogranulomas though not so common, may occur in older age group and should always be in mind while making a diagnosis of a disease of similar morphology.